Changing Narratives of Jan and Maria Malisz’s Case (1933): Social, Legal and Cultural Perspectives - Jaworska-Biskup, Katarzyna; Peno, Michał (Porównania, 2023)
In 1933, Cracow was the scene of a brutal murder of three people: Helena and Michał Süskind and Walenty Przebinda, a postman. The bloody slaughter of the victims had taken place on Pańska street, in the city centre of Cracow. It was soon revealed that the crime had been perpetrated by the impoverished couple Jan and Maria Malisz. The speedy public trial of the culprits ended with two death sentences. Jan was hanged after rendering the verdict. His wife Maria escaped death by being pardoned by the president of Poland, Ignacy Mościcki (1867–1946). The case triggered the attention of many commentators. It was widely described in the press. It was also the topic of many books and papers, especially documentaries dealing with the theme of famous crimes in Poland in the 1930s. Despite the great interest in the case, no critical research has been devoted thereto, which is the rationale behind this scholarly contribution. The paper discusses how the case of Jan and Maria was framed in various narratives. The analysis combines social, legal and popular culture perspectives and entails such sources as court documents, the press coverage, post-war legal documentaries, and Internet forums, as well as the 1972 film Na Wylot directed by Grzegorz Królikiewicz (1939–2017). It is of particular interest to show how the case was presented in the source material. The paper also investigates the effect of such a presentation on the changing perception of the case in question. The case prompts discussion on issues such as female versus male crime, partnership in crime, victim-oriented versus perpetrator-oriented approaches, and the intersection between legal and popular culture narratives. As far as the methodology is concerned, it employs Kaarlo Tuori’s theory of three levels of the law.